Investiční modely v prostředí kapitálových trhů - Komárek, Lukáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Diplomová práce pojednává o modelech investičních strategií na kapitálových trzích. Na základě rešerše prostředí finančních trhů, analýzy dostupných finančních produktů a za pomoci podpůrných informačních prostředků, jsou vypracovány a nasimulovány tři rozdílné investiční strategie – riziková dynamická strategie, střední vyvážená strategie a stabilní konzervativní strategie. Výstupem práce je investiční dotazník, který slouží k výběru vhodné investiční strategie, a tři modely investičních strategií včetně zhodnocení. Samotné vyhodnocení investičního dotazníku probíhá pomocí fuzzy logiky.

This thesis deals with models of investment strategies in an environment of capital markets. Based on the research environment of financial markets, analysis of available financial products and the help of supporting information resources, there are developed and simulated three different investment strategies – risk dynamic strategy, medium balanced strategy and a stable conservative strategy. The output of work is an investment questionnaire, which is used to select appropriate investment strategies, and three models of investment strategies, including evaluation. Investment evaluation itself is performed by fuzzy logic.
The Investment Models in an Environment of Capital Markets
Keywords: Investiční strategie; akcie; podílové fondy; spořicí účty; model; simulace; Visual Basic .NET; fuzzy logika; Investment strategy; shares; mutual funds; savings accounts; model; simulation; Visual Basic .NET; fuzzy logic